Handbook of marketing analytics : methods and applications in marketing management, public policy, and litigation support - Mizik, Natalie; Hanssens, Dominique M. (Edward Elgar Publishing, 2018)
"The Handbook of Marketing Analytics showcases analytical marketing methods and their high-impact real-life applications in marketing management, public policy, and litigation support. Fourteen chapters present an overview of specific marketing analytic methods in technical detail, while 22 case studies present thorough examples of the use of each method. The contributors featured are recognized authorities in their fields. Multidisciplinary in scope, this Handbook covers experimental methods, non-experimental methods, and their digital-era extensions. It explores topics such as classical and Bayesian econometrics, causality, machine learning, optimization, and recent advancements in conjoint analysis. This standout collection of analytical methods and application will be useful and educational for all readers, whether they are academics or practitioners in marketing, public policy, or litigation."--Resumé vydavatele
Keywords: marketing; analýza dat; zpracování dat; marketingový výzkum; data analysis; data processing; marketing research; příručky; handbooks and manuals